Ancestor centrism: A Philosophical Paradigm for Transdisciplinary Research (A) - Abu Tia Jambedu (PhD cand.); Badigamsira Inusah Abdul Majeed; Prof. David Millar (Zien Journals, 2024)
This research explores Ancestorcentrism, a transdisciplinary research framework emphasising respect for diversity, knowledge development, clear values, practical applications, and cultural sensitivity. It argues for decolonising knowledge by highlighting the perspectives of the Mossi-Dagbamba people of West Africa. The study employs transcendental philosophy and qualitative methods, including interviews and observations, to understand the lived experiences of the Mossi-Dagbamba in relation to Ancestorcentrism. Considering their social, cultural, and spiritual context, this framework values indigenous knowledge, science, philosophy, and development
Keywords: Mossi-Dagbamba; Ancestorcentrism; Ontology; Worldview